Periodontal Parameters and Anti-Cardiolipin Antibodies Following Periodontal Therapy in Chronic Periodontitis - Wan Mohamad, Wan Majdiah; Saad, Noor Rashidah; Zainuddin, Siti Lailatul Akmar; Taib, Haslina (UI Scholars Hub, 2021)
Anti-cardiolipin (anti-CL) antibodies are autoantibodies which are directed against cell membrane phospholipids. A significant number of periodontitis patients showed positive for anti-CL antibody. Objective: This study aimed to determine the periodontal parameters and anti-CL antibodies levels before and after non-surgical periodontal therapy in chronic periodontitis. Methods: This cross-sectional study had been carried out at Periodontal Clinic, Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan, Malaysia. Thirty five chronic periodontitis (CP) and 39 non-periodontitis (NP) patients underwent clinical periodontal examination at baseline. Plaque index (PI), gingival index (GI), periodontal pocket depth (PPD), and clinical attachment loss (CAL) were measured. Scaling and polishing was performed and blood samples were taken for IgG and IgM anti-CL antibodies analysis. Re-evaluationwas performed four weeks after initial therapy. CP patients were re-examined, all periodontal parameters were recorded and blood samples were taken for reassessment of IgG and IgM anti-CL antibodies. Results: Significant difference means of PI(p=0.001), GI (p=0.000), PPD (p=0.000) and, CAL (p=0.000) were found between CP and NP groups. All periodontal parameters were significantly reduced (p≤0.05) after four weeks of therapy. The mean levels of IgG and IgM anti-CL antibodies at baseline were significantly higher in CP than NP group (IgG=4.46 vs 3.22, p=0.002; IgM=3.28 vs 2.57, p=0.019). No significant difference of the median levels of IgG (p=0.82) and IgM anti-CL antibodies (p=0.35) following therapy. Conclusion: All periodontal parameters were significantly reduced following periodontal therapy. Higher level of Anti-CL antibodies in CP indicates stimulation of autoantibodies production by periodontal infection. Nonetheless no significant changes of this anti-CL antibodies levels despite significant reduction of the clinical parameters after periodontal therapy.